Analysis of Students' Communication Skills in 21st Century Learning: Application of 4C-Based Problem Based Learning (PBL) in Elementary Schools - Fajar Puji Hardono; Sri Yamtinah; Peduk Rintayati (Teknodika, 2025)
This study aims to analyze the communication skills of elementary school students in the context of 21st century learning through the application of the 4C-based Problem Based Learning (PBL) model. The research method used is a qualitative approach with a case study design. The subjects of this study were 5th grade students at SD Negeri Bekonang 02, Mojolaban District in 2024/2025. Data collection used observation, interview, and documentation techniques, and was analyzed using the Miles and Huberman interactive model. The results showed that the application of 4C-based PBL can improve students' written communication skills in science learning. Students become more active in expressing several opinions and writing experimental reports. Learning in elementary schools should be contextual, collaborative, and also problem-based in order to support skilled communication skills in the classroom.